Old Stereotypes Die Hard? Public Perceptions and Political Outcomes of Perceived Immigrant Criminality - Farkas, Natalie (Université d'Ottawa | University of Ottawa, 2017)
How does research on the relationship between immigration and crime differ from public perception? What are the implications of this continued association between immigrants and crime?